Fat and lean tissue accretion in relation to reward motivation in children. (1st January 2017) - De Decker, Annelies; De Clercq, Bart; Verbeken, Sandra; Wells, Jonathan C.K.; Braet, Caroline; Michels, Nathalie; De Henauw, Stefaan; Sioen, Isabelle
Abstract: 'Reward sensitivity' explains inter-individual differences in the motivation to obtain rewards when reward cues are perceived. This psychobiological trait has been linked to higher consumption of palatable food when exposed to palatable food cues. The current study aims to examine if reward sensitivity explains differences in patterns of fat and lean tissue accretion over time in children. A longitudinal observational study with measurement waves in 2011 (baseline), 2012, 2013, and 2015 was conducted. The sample was a population-based Flemish cohort of children (n = 446, 50% boys and 5.5–12 years at baseline; 38.8% of the baseline sample also participated in 2015). Baseline reward sensitivity of the children was assessed by parent ratings on the Drive subscale of the Behavioral Inhibition System/Behavioral Approach System scales. Age- and sex-independent Fat and Lean Mass Index z-scores (zFMI and zLMI respectively) were computed for each study wave based on air-displacement plethysmography. In girls, but not boys, reward sensitivity was positively associated with the baseline zFMI and zLMI (95% confidence intervals of unstandardized estimates: 0.01 to 0.11 and 0.01 to 0.10 respectively, P values 0.01 and 0.02 respectively). Further, reward sensitivity explained 14.8% and 11.6% of the change in girls' zFMI and zLMI respectively over four years: the zFMI and zLMI increased and decreased respectively in high reward sensitive girls (95% confidence intervals of unstandardized estimates: 0.01 to 0.11 and −0.12 to −0.01 respectively, P values 0.01 and 0.02 respectively). Hence, girls high in reward sensitivity had significantly higher adiposity gain over four years parallel with lower increase in lean mass than was expected on the basis of their age and height. These results may help to identify appropriate targets for interventions for obesity prevention.